The Development of Mobile Augmented Reality Korean Language Learning Application: KoreAR - Tan, Qiu Hua; Che Samihah Che Dalim (Applied Information Technology And Computer Science, 2024)
Korean language is the official language of South Korea and North Korea, and Hangul is used as the alphabet and writing system. Hangul helps in the learning and comprehension of the Korean language for both native and non-native Korean speakers. However, the existing Korean language learning applications for learning Hangul lacks interactive elements, and only few are implemented with augmented reality (AR) technology. Therefore, this objective of this project is to develop an augmented reality mobile Korean language learning application that helps to learn Hangul. The target users for this project are university students. The development of KoreAR application is based on the Multimedia Mobile Content Development (MMCD) methodology. Besides, based on the user acceptance test, an average score of 88.42 were obtained, which is within the acceptable range according to the System Usability Scale (SUS). To sum up, the application is expected to help target users learns the basic of Hangul, by implementing markerless AR technology.